The Vulnerability of Health Infrastructure to the Impacts of Climate Change and Sea Level Rise in Small Island Countries in the South Pacific - Subhashni Taylor (SAGE Publishing, 2021)
Anthropogenic climate change and related sea level rise will have a range of impacts on populations, particularly in the low lying Pacific island countries (PICs). One of these impacts will be on the health and well-being of people in these nations. In such cases, access to medical facilities is important. This research looks at the medical facilities currently located on 14 PICs and how climate change related impacts such as sea level rise may affect these facilities. The medical infrastructure in each country were located using information from a range of sources such as Ministry of Health (MoH) websites, World Health Organization, Doctors Assisting in South Pacific Islands (DAISI), Commonwealth Health Online, and Google Maps. A spatial analysis was undertaken to identify medical infrastructure located within 4 zones from the coastline of each country: 0 to 50 m, 50 to 100 m, 100 to 200 m, and 200 to 500 m. The findings indicate that 62% of all assessed medical facilities in the 14 PICs are located within 500 m of the coast. The low-lying coral atoll countries of Kiribati, Marshall Islands, Nauru, Palau, Tokelau, and Tuvalu will be highly affected as all medical facilities in these countries fall within 500 m of the coast. The results provide a baseline analysis of the threats posed by sea-level rise to existing critical medical infrastructure in the 14 PICs and could be useful for adaptive planning. These countries have limited financial and technical resources which will make adaptation challenging.